SEISMOLOGICAL MAPS OF NORTH EURASIA INCLUDING EARTHQUAKE PREDICTION DATA: AN APPROACH, MAPPING TECHNIQUE, AND RESULTS - Polyakova T.P.; Medvedeva N.S. (My University, 2000)
A new approach is proposed for mapping seismicity parameters. It incorporates the scale of the seismic process involved (precursory areas of large earthquakes) and interaction of seismicity at great distances. The concepts of contemporary seismology are used to formulate the principles of this approach to be implemented with the help of a mapping technique (scanning) producing a set of seismological maps for North Eurasia. No 'failures-to-predict' emerged on testing this approach, the mapping technique, and forecast maps based on extensive factual material from seismic regions of North Eurasia. All 'unexpected' earthquakes which occurred in 1976-1997 are consistent with the assessments of seismic potential made either before the events or retrospectively.